2020
DOI: 10.1038/s41598-020-72232-y
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers and renin-angiotensin system inhibitors in acute myocardial infarction managed with inhospital coronary revascularization

Abstract: Pivotal trials of beta-blockers (BB) and angiotensin converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARB) in acute myocardial infarction (AMI) were largely conducted prior to the widespread adoption of early revascularization. A total of 15,073 patients with AMI who underwent inhospital coronary revascularization from January 2007 to December 2013 were analyzed. At 12 months, BB was significantly associated with a lower incidence of major adverse cardiovascular events (MACE, adjusted HR 0.80, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In this regard and through its effects in modulating post-MI remodeling, tropoelastin therefore bears some similarity to drugs historically used as subacute therapeutics, such as angiotensin converting enzyme inhibitors. 62 Following the subacute effects of MI and during progressive heart failure, the heart undergoes compensatory LV dilatation. 63 Therefore, to understand the effects of tropoelastin in a more chronic setting, future studies will likely concentrate on injecting tropoelastin 2 to 3 weeks post-MI with longer term (≥6 months) functional studies to elucidate its effects on LV dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard and through its effects in modulating post-MI remodeling, tropoelastin therefore bears some similarity to drugs historically used as subacute therapeutics, such as angiotensin converting enzyme inhibitors. 62 Following the subacute effects of MI and during progressive heart failure, the heart undergoes compensatory LV dilatation. 63 Therefore, to understand the effects of tropoelastin in a more chronic setting, future studies will likely concentrate on injecting tropoelastin 2 to 3 weeks post-MI with longer term (≥6 months) functional studies to elucidate its effects on LV dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Cardiology have proposed several conditions to be considered as atherosclerotic cardiovascular disease risk enhancers, including inflammatory disease such as rheumatoid arthritis or human immunodeficiency virus infection [ 28 ]. Established risk scores have also been shown to underestimate cardiovascular risk within these specific patient populations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Hence, we propose that further research is needed to ascertain the value of adding cancer as a variable to the ASCVD score, as well as to identify and include relevant cancer-related variables to improve its applicability within patients with prior cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Singapore Myocardial Infarction Registry consists of data from patients diagnosed with AMI from 2007 across all hospitals within the country. Specialized coordinators collected data including patient demographics, clinical presentation, medications, laboratory and procedural parameters [ 15 ]. As individual-level blood pressure values were only available within the registry from 2017, data on blood pressure was extracted from hospital-level databases from two centers and merged with the national registry for the years 2007 to 2016.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Rodriguez-Palomares et al concluded that assessment of left ventricular remodeling at 6 months did not increase the prognostic value of the principal cardiac magnetic resonance (CMR) derived variables provided by early CMR 23 . Since access to CMR is limited, we believe that this nomogram, once validated, could offer a widely available, low-cost alternative to predict patients at risk of developing pathologic left ventricular remodeling and we are doing so in a very early stage of myocardial infarction (12 hours after reperfusion has been achieved) despite administering optimal medical therapy and revascularization 24 .…”
Section: Discussionmentioning
confidence: 99%